Katekese Untuk Membangkitkan Antusias dan Keaktifan OMK Paroki Maria Bunda Karmel, Probolinggo - Ignasius Budiono; Juli Antonius Sihotang; Antonius Denny Firmanto (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2022)
This paper departs from the author's anxiety to see the lack of enthusiasm and activeness of young people, especially the MBK parish OMK organization, Probolinggo in participating in church activities. The author collects data from the database of parishioners (the total number of young people), answers to questions on google forms, and the author's experience when he was one of the supervisors of OMK, Probolinggo. All the data collected were then analyzed using a qualitative-descriptive method. The author will show the results of the research based on the data that has been obtained through the MBK parish, various answers from young members of OMK, and the author's own observations. Through these data, it was found that there were gaps within the organization itself, and the time mismatch of existing activities with their respective statuses and activities. Not yet compact, lack of enthusiasm, and the activeness of OMK members is what then makes many young people in MBK parish not interested in becoming OMK members. Based on the formulation of the existing problems and the findings, it can be concluded that good, in-depth, and sustainable catechesis is very influential for young people to create cohesiveness in the OMK organization, so that they respect each other, relate closely, and are full of brotherhood with one another.